Online Group Supervision as Pedagogy: A Qualitative Inquiry of Student Mental Health Nurses’ Discourses and Participation - Howard, Vickie; Peirson, Jane (Issues in Mental Health Nursing, 2025)
This study explored online group clinical supervision participation, as a component of pre-registration education following mental health nursing students’ clinical placements. Clinical supervision has historically been valued as a supportive strategy by healthcare professionals to develop practice and competence and prevent burnout. As many student nurses do not have access to clinical supervision via practice areas as a standardised process, their experiences of engaging in or benefitting from clinical supervision are wide-ranging. In view of this, we are identifying a theory-practice gap between theoretical knowledge and practice experience. This study incorporated a qualitative inquiry using reflexive thematic analysis and applying poststructural theoretical perspectives. Online group clinical supervision was delivered to student mental health nurses whereby focus groups followed to discuss their views, understandings and experiences of online group clinical supervision. This was against a back drop of Covid-19 lockdown restrictions. Thematic synthesis identified two main areas for improving participation and pedagogy comprising; Improving Confidence and Trust in (Online) Participation and The Need for Familiarity in CS Participation and Understanding. Thematic and poststructural analysis demonstrated participants’ positive outlooks on the values of clinical supervision, whilst also identifying the finer nuances of the differences in accessing group clinical supervision through an online format. This study adds to the literature on using group clinical supervision within the student mental health nurse population by identifying the benefits of group clinical supervision for student nurses. It has additionally found that the silences and inhibitions surrounding online participation are important areas for further research.